The gender-differentiated impact of climate variability on production possibilities: Evidence from cereal production in Mali - Dillon, Andrew; Gill, Joshua (International Food Policy Research Institute, 2014)
This policy note summarizes research into the gender-differentiated impacts of climatic changes on farmers’ production possibilities using a representative sample of farmers in rainfed and irrigated areas of the Segou region of Mali during the 2009 and 2012 growing seasons.